Urban restructuring in post-war contexts: the case of Sarajevo - Martín-Díaz, Jordi (Hungarian Geographical Bulletin, 2014)
The transition from state-socialism to capitalism has not been the only process reshapingthe urban landscapes in Central and Eastern Europe but some cities were affected by war destructions, like in the Caucus region or in the former Yugoslavia. The case study of Sarajevo, the capital of Bosnia and Herzegovina, is helpful to understand how the urban transformation is performed in post-war contexts, an arena neglected in the current literature on post-socialist cities. This paper aims at exploring the interplay between postsocialist urban restructuring and the peace-building process. It presents results of a series of fieldworks conducted in Sarajevo in 2010 and 2013. It is argued that in spite of the liberal policies implemented by the international community and the belated physical renewal, the transition from socialism to capitalism has been continuously undermined by the local power reconfiguration carried out during the war. The paper analyses the restructuring policies of the post-war period and its impact on the urban spatial structure. The first two sections focus on the urban restructuring processes of post-socialist cities also in post-war contexts, in which the nature of the internationally-led reconstruction and peace-building is analysed as differential processes. Finally, both processes are considered in the case of Sarajevo in relation to the transformation of its urban structure.